Application of Falou as Independent Learning Medium for Practicing German Speaking Skills at SMAN 1 Wonoayu Sidoarjo - Putri, Aisha Aurelie; Indriwardhani, Sri Prameswari (Journal DaFIna - Journal Deutsch als Fremdsprache in Indonesien, 2024)
The aim of this study is to describe students' use of and reactions to the Falou application as a self-learning medium for speaking skills practice in German. The method used in this study is a descriptive qualitative research with students of class XI-7 SMAN 1 Wonoayu, a total of 31 students. The observation was conducted on March 25, 2024 for one session, the results of the observation of the use of the Falou application went smoothly and the students were very enthusiastic, although they were limited in using the application by the Internet network and a slight difference in appearance between Android and IOS. The results of the Falou application questionnaire are very suitable for beginners in learning German, especially for practicing pronunciation and helping students to learn and understand the material on their own and everyday expressions related to getting to know the subject matter.